2018
DOI: 10.3389/fpsyg.2018.01963
|View full text |Cite
|
Sign up to set email alerts
|

First Language Attrition and Dominance: Same Same or Different?

Abstract: We explore the relationship between first language attrition and language dominance, defined here as the relative availability of each of a bilingual’s languages with respect to language processing. We assume that both processes might represent two stages of one and the same phenomenon (Schmid and Köpke, 2017; Köpke, 2018). While many researchers agree that language dominance changes repeatedly over the lifespan (e.g., Silva-Corvalan and Treffers-Daller, 2015), little is known about the precise time scales inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 84 publications
3
23
0
Order By: Relevance
“…Finally, for the blocked‐cyclic naming task, pre‐experiment familiarization provided an opportunity to reestablish the pictures’ names in the target language, which is conservative with respect to our claims of a shift in language dominance. That is, although some have suggested that speakers can easily overcome the effects of language attrition (e.g., Köpke & Genevska‐Hanke, 2018)—via processes that experimental psychologists might identify with repetition priming (Scarborough, Cortese, & Scarborough, 1977) and error‐proportional incremental learning (Oppenheim et al., 2010)—any resulting attenuation of L1 attrition would both make it more difficult detecting a change in dominance and be insufficient to explain children's continued L1 improvement in both tasks and all measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, for the blocked‐cyclic naming task, pre‐experiment familiarization provided an opportunity to reestablish the pictures’ names in the target language, which is conservative with respect to our claims of a shift in language dominance. That is, although some have suggested that speakers can easily overcome the effects of language attrition (e.g., Köpke & Genevska‐Hanke, 2018)—via processes that experimental psychologists might identify with repetition priming (Scarborough, Cortese, & Scarborough, 1977) and error‐proportional incremental learning (Oppenheim et al., 2010)—any resulting attenuation of L1 attrition would both make it more difficult detecting a change in dominance and be insufficient to explain children's continued L1 improvement in both tasks and all measures.…”
Section: Discussionmentioning
confidence: 99%
“…One underappreciated consequence of this error‐proportionality is that, although the network's connections reflect the cumulative effects of all its previous experience—and can thus account for basic frequency effects as well as “weaker links”‐related phenomena (Gollan, Montoya, Cera, & Sandoval, 2008)—they disproportionately reflect its most recent experience. It can therefore account for both relatively rapid shifts in language dominance and attenuation of L1 attrition upon re‐immersion in an L1 environment (Köpke & Genevska‐Hanke, 2018), as well as the particular importance of bilinguals’ current language use in predicting their relative abilities (Bedore et al., 2012; Unsworth, 2013). Thus, switching entirely to a L2 may lead to the gradual loss of a L1, but occasionally interleaving episodes of L1 use may be sufficient to not only undo the damage but even reverse it (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring and controlling for language dominance is crucial in research, but also holds psychological and societal importance because of its connections with language attrition and language loss (for an overview, see Köpke and Genevska-Hanke 2018). This project aimed to (1) measure language dominance in bilingual speakers of Italian and Croatian who were perceived as balanced, and (2) identify psychological and sociological factors relevant for determining language dominance.…”
Section: Language Dominance Of Bilingual Speakers Perceived As Balancedmentioning
confidence: 99%
“…Our understanding of the conditions under which changes effected by language attrition may be reversed, to date, is extremely limited for practical reasons, even though it has long been one of the more tantalizing questions in the field. However, a study by Genevska-Hanke revealed that the proportion of overt pronominal subjects realized in the first-language (L1) Bulgarian of a Bulgarian–German bilingual with 17 years of residence in Germany, having been significantly higher than that of monolingual Bulgarian controls, not only dropped back to native levels after a 3-week stay in Bulgaria (Genevska-Hanke, 2017) but also remained at those levels during a further 5 years of immersion in Germany (Köpke and Genevska-Hanke, 2018). Findings such as this do somewhat undermine the assumption that the settings and feature bundles of the native language can be modified by the same mechanisms as are used for grammar building, and throw up the question of whether the model needs to make some kind of further provision for a trace or underlying ‘phantom’ grammar, maintaining the original representation and allowing the speaker to revert to it with far less input-to-intake events than needed to modify it in the first place.…”
mentioning
confidence: 99%